Conservation for Survival / An Ecological Strategy - Curry-Lindahl Kai (William Morrow And Company, Inc, 1972)
This book tries to cover the basic conservation problems relative to the present world situation, in which man's conduct and treatment of the environment have led to an ecological crisis. Foreword, Conservation for Survival, The Air, The Sea, Fresh Water, The Soil, The Vegetation, The Animals, Man, Is Conservation a Loosing Battle?, Continental Problems of Today, The Future, An Ecological Strategy, Glossary, Bibliography, Index.